Implementation of Smart Governance Concept Policy in Bantul Regency - Methafiani Farikha (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2019)
This aims to know about what is the implementation of smart governance concep policy in Bantul Regency. This research uses descriptive qualitative research methods. Bantul Regency Government provides a smart city application to facilitate community participation in reporting an incident that occurs in the Bantul Regency environment. This application was created to be a means of fast and effective information between the public and the government. Not many people know, and there are some features that are either not understood by the community or do not facilitate the work done by LAPOR! Staff. Most complaints in Bantul Regency are dominated by complaints about infrastructure, the environment, bureaucratic reform and governance, population administration and several other problems. What is expected from the results of this study is the LAPOR! this becomes a bridge to connect complaints and aspirations of the community with relevant agencies, so that the issues raised can be conveyed and get a quick and appropriate treatment.